Curcumin analogues inhibit phosphodiesterase‐5 and dilate rat pulmonary arteries. (1st September 2014) - Kruangtip, Oraya; Chootip, Krongkarn; Temkitthawon, Prapapan; Changwichit, Kanokwan; Chuprajob, Thipphawan; Changtam, Chatchawan; Suksamrarn, Apichart; Khorana, Nantaka; Scholfield, C. Norman; Ingkaninan, Kornkanok
Abstract Objectives Phosphodiesterase (PDE)‐5 inhibitors are useful as vasodilators for the treatment of pulmonary arterial hypertension. We aimed to study curcumin analogues for PDE5 inhibitory activity and vasorelaxation of rat pulmonary arteries. Methods Three natural curcuminoids (1–3) and six synthetic analogues (4–9) were tested for PDE5 and PDE6 inhibitory activities using enzymatic radioassay. Their vasorelaxation was measured using freshly isolated segments of rat pulmonary artery and aorta. Key findings Curcuminoids (1–3) mildly inhibited PDE5 (half maximal inhibitory concentration (IC50) = 18 µm): the metamethoxyl of curcumin was important for PDE5 inhibition. But hydroxyl rearrangements, removing both methoxyls and one ketomethylene, yielded the potent 7 and 9 (IC50 = 4 µm) (compared with sildenafil, IC50 = 0.03 µm). Only 1, 3 and 4 were PDE5 selective over PDE6. Triazole‐carboxylic addition provided water‐solubility while preserving potency. All analogues possessed concentration‐dependent vasorelaxant activity on pulmonary arteries (40% of maximal effective concentration (EC40) = 29–90 µm, maximum response = 60–90% at 300 µm), while compounds (1–8) were weakly acting in aorta (maximum response <40%). Only demethoxycurcumin (2) and analogues 5, 8, 9 had endothelium‐dependent actions. Sildenafil was highly potent (EC40 = 0.04 µm) and highly endothelium dependent in pulmonary artery but weak on intact aorta (EC40 = 1.8 µm). Activity profiles suggest actions through additional cell pathways for promoting vasorelaxation. Conclusions Curcumin analogues are potential leads for developing efficacious and selective PDE5 inhibitors and other pathologies of pulmonary hypertension.